EFFICACY AND SAFETY OF PNEUMATIC LITHOTRIPSY WITH LASER LITHOTRIPSY IN THE TREATMENT OF URETERAL STONES <20 MILLIMETERS IN CHILDREN: A SYSTEMATIC REVIEW AND META-ANALYSIS - Irsayanto, Danang; Yatindra, Ida Bagus Gde Tirta Yoga; Setiawan, Muhammad Rifki; Salsabila, Sirin; Renaldo, Johan; Wirjopranoto, Soetojo (Journal of Ayub Medical College Abbottabad, 2024)
Background: Ureterorenoscopy (URS) in treating ureteral stones in children is preferred for >10 mm-sized stones. Pneumatic lithotripsy is often used, but laser lithotripsy is gaining more popularity over the years, as it is considered better in terms of safety and efficacy. However, no previous meta-analysis has discussed the comparison of these two modalities. This meta-analysis compared pneumatic and laser lithotripsy in children with ureteral stones. Methods: This meta-analytic study followed the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) guidelines. Inclusion studies were retrieved by thoroughly searching Pubmed, Scopus, ScienceDirect, Web of Science, and Embase databases, focusing on the comparative intervention of pneumatic and laser lithotripsy in the paediatric population. Result: Study analysis showed that laser lithotripsy had a significantly higher stone-free rate (OR: 2.06; 95% CI: 1.06 - 4.00; p=0.03) and lower stone retropulsion (OR: 0.37; 95% CI: 0.16-0.87; p=0.02) compared to pneumatic lithotripsy. However, mean operative time (MD: 2.33; 95% CI: -4.09-8.74; p=0.48), length of stay (MD: -0.17; 95% CI: -0.36-0.02; p=0.08), post-operative fever (OR: 1.50; 95% CI: 0.48-4.66; p=0.48), and ureteral injury (OR: 0.43; 95% CI: 0.08-2.48; p=0.35) was not different between the two groups. Conclusion: A higher stone-free rate (SFR) and a lower incidence of stone retropulsion can be achieved using laser lithotripsy instead of pneumatic lithotripsy for treating ureteral stones in children.